2016
DOI: 10.1111/jre.12380
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histopathologic analysis of the effects of periodontitis on left ventricular heart tissues of rats

Abstract: histopathologic analysis of the effects of periodontitis on left ventricular heart tissues of rats.Background and Objective: Current epidemiological works have suggested that chronic infections, such as periodontitis, are associated with an increased risk of cardiovascular diseases, including hypertrophy and heart failure. However, mechanisms behind the association are not known. The aim of this study was to evaluate the effects of periodontitis on the serum lipid levels, inflammatory marker levels and left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 46 publications
(84 reference statements)
2
26
0
2
Order By: Relevance
“…atrium, myocardium and aortic valve) along with the inflammatory biomarkers could further explain the connection of periodontitis and LV dysfunction (Ziebolz et al., 2018). In rats with ligature‐induced periodontitis, activated monocytes are more likely to adhere to aortic endothelia, yet these inflammatory cells could proceed to the myocardium and induce inflammatory and hypertrophic responses in the LV tissues (Kose et al., 2017; Miyajima et al., 2014). Furthermore, the mice injected with a low dose of Porphyromonas gingivalis lipopolysaccharide exhibit an increased level of cardiac troponin I and impaired cardiac function (Deleon‐Pennell, de Castro Bras, & Lindsey, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…atrium, myocardium and aortic valve) along with the inflammatory biomarkers could further explain the connection of periodontitis and LV dysfunction (Ziebolz et al., 2018). In rats with ligature‐induced periodontitis, activated monocytes are more likely to adhere to aortic endothelia, yet these inflammatory cells could proceed to the myocardium and induce inflammatory and hypertrophic responses in the LV tissues (Kose et al., 2017; Miyajima et al., 2014). Furthermore, the mice injected with a low dose of Porphyromonas gingivalis lipopolysaccharide exhibit an increased level of cardiac troponin I and impaired cardiac function (Deleon‐Pennell, de Castro Bras, & Lindsey, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that persistent inflammation could lead to adverse effects on heart contractility, inducing hypertrophy and apoptosis . Moreover, experimental study suggested that periodontitis could induce monocytes to adhere to aortic endothelium and proceed to myocardium, inducing inflammatory and hypertrophic responses in the LV tissues …”
Section: Discussionmentioning
confidence: 99%
“…43 Moreover, experimental study suggested that periodontitis could induce monocytes to adhere to aortic endothelium and proceed to myocardium, inducing inflammatory and hypertrophic responses in the LV tissues. 44 Currently, there is no global consensus on the criteria to determine the severity of periodontitis in DM subjects. In the present study, <10% of the participants were classified as no or mild periodontitis according to the CDC-AAP case definition, 45 owing to the high prevalence and extensive nature of periodontitis in these medically compromised individuals.…”
Section: Cadmentioning
confidence: 99%
“…Apical periodontitis may occur as a tissue response to pulpal infection following from dental caries, trauma, attrition from mastication, and abrasion from the use of teeth as tools . There is growing evidence that inflammatory diseases and infections may be the cause of and related to the emergence of cardiovascular problems . As an oral disease, AP is known to be a potential risk factor for cardiovascular diseases .…”
mentioning
confidence: 99%